Inflation-Unemployment Dynamics in the Context of the Phillips Curve - Yoshimori, Masaaki (Journal of Reviews on Global Economics, 2026)
This paper studies how US inflation dynamics have evolved as labor-market institutions weakened and expectations became more central to price-setting. Using quarterly data from 1984Q1–2023Q4, we estimate Phillips-Curve-style regressions that allow inflation to depend on expected inflation, lagged inflation, and interactions between unemployment and union density, and we complement these results with a multivariate vector autoregression (VAR) to trace dynamic responses. Three findings emerge. First, inflation is best explained by a joint expectations–persistence component: expected inflation, lagged expectations, and lagged inflation together account for substantially more variation in inflation than specifications based on unemployment or the output gap alone. Second, interaction between the unemployment–union-density is economically meaningful, consistent with weaker collective bargaining dampening the wage channel and contributing to a flatter inflation–slack relationship. Third, VAR impulse responses indicate that expectation shocks transmit to inflation primarily over short horizons, while inflation persistence remains a dominant propagation mechanism. These results imply that inflation stabilization increasingly depends on anchoring expectations and understanding labor-market structure, rather than relying on slack measures as sufficient statistics for inflationary pressure.